Cost and Benefit Analysis of ERP Implementation and Change Management in the Omani government Sector - Al-Bulushi, Sharifa (2009)
ERP implementation is becoming one of the key challenges organizations face now a days. With the increasing competitive business environment and need for providing best in class products and services, the demand for ERP implementation is growing. There is not one defined approach to implement ERP system, in order to yield the desired and expected results. Further, ERP are of the shelf packages which offer integrated applications and enhance the quality of day to day activities of an organization. ERP packages offer major improvements of business process re-engineering and enforce the built in best practices. Understanding the implementation process through a balanced perspective will therefore prevent any unpleasant surprises, and will ensure and guide the change process to be embedded in a painless fashion. This drastic change requires appropriate change management techniques. However, implementing ERP requires a lot of time and effort to achieve the objectives and avoid failure. This paper proposes an integrative framework for ERP implementation based on an extensive review of literature on Cost and benefit analysis of ERP implementation, ERP effect on business processes and change management techniques. Further, examining two case studies to assess major trends in ERP implementation and change management approaches in the government sector in Oman.